Rapt in the name : the Ramnamis, Ramnam, and untouchable religion in Central India - Lamb, Ramdas (SUNY series in Hindu studies., 2002)
"In Rapt in the Name, Ramdas Lamb provides an intriguing account of the Ram bhakti tradition in India. Less well-known in the West than the tradition of devotion to Krishna, the Ram tradition is an important component of Hinduism. Ram is the most-worshipped form of the divine in North India today and has long been particularly important to those of the lower castes throughout India. Lamb explores both the evolution of the tradition and the rise of lower caste religious movements devoted to Ram, specifically the Ramnami Samaj, an Untouchable religious movement in Central India."--Jacket